The role of political marketing and its importance in Barisan Nasional at Malaysia general election - Koay, Hean Wei; Khairiah, Salwa Mokhtar (Technium Social Sciences Journal, 2022)
This study discusses the political marketing tools based on the research in Barisan Nasional (BN) at Malaysia general election. According to the Malaysian law, the date of the last election and subsequent election is to be held at 5-year intervals. Thus, after GE12 in 2008, GE13 was held in 2013. Since 1969 from Alliance coalition to 1973 BN coalition never lost a general election in parliamentary constituency. The political tsunami in GE12 BN won 140 seats in Dewan Rakyat out of 222 seats, opposition parties such as Pakatan Rakyat (PR) won 82 seats out of 222 Dewan Rakyat of seats in Malaysia (Election Commission of Malaysia, 2008, 2013, 2018). The GE13 result was almost the same as GE12 in which BN won 133 seats in Dewan Rakyat or 47.38% of the votes. Pakatan Rakyat (PR) won the support for 89 seats in Dewan Rakyat or 50.87% of the votes. This is first time BN won in the general election but with less of the votes. In GE12 and GE13 voters started to support the opposition rather than BN. Specifically, direct voter contact, indirect voter contact, dominant party, party leader, gerrymandering, malapportionment, re-delineation, first-past-the-post system (FPTP) are the political marketing tools implement by BN. This paper discusses about political marketing tools employed by BN during general election. Therefore, this paper can provide information to political parties and help them to identify the suitable political marketing tools for coming elections.